Public Networked Discourses in the Ukraine-Russia Conflict: 'Patriotic Hackers' and Digital Populism. - Lokot, Tetyana (Irish Studies in International Affairs, 2017)
This paper explores the self-presentation and online discursive practices of grassroots hacker collectives on both sides of the Ukraine-Russia conflict within a larger geopolitical climate of a contested globalisation agenda and a growing fear of cyber warfare. Both pro-Russian and pro-Ukrainian hacker groups engage in DDoS attacks, malware distribution and leaking stolen information from the opposing side. They also use social media to enter the broader political discourse around the conflict. The paper analyses the Twitter posts of both collectives to reveal key modes of online practices and key discursive themes in the context of the conflict, such as political activism, information warfare, hacker ethics and patriotism. The study elucidates how these groups use their social media presence to construct a 'patriotic hacker' identity for themselves, to delegitimise their opponents and ultimately, to connect to the broader populist discourse, where issues of patriotism, sovereignty and nationhood are contested.